2007
DOI: 10.1071/ea07093
|View full text |Cite
|
Sign up to set email alerts
|

Sheep genotype, age and muscle type affect the expression of metabolic enzyme markers

Abstract: The objective of this study was to determine whether genotype, age (4, 8, 14 and 22 months), sex (ewe and wether) and muscle type influence ovine (n = 587) muscle metabolic characteristics. The genotypes represented were Poll Dorsetgrowth × Border Leicester Merino, Poll Dorsetgrowth × Merino, Poll Dorsetmuscling × Merino, Merino × Merino and Border Leicester × Merino. Between 4 and 22 months of age, myoglobin concentration within all muscles and all genotypes doubled, with the bulk of this response occurring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 18 publications
3
17
0
2
Order By: Relevance
“…Berge et al (2003) reported a simple correlation of 0.66 between lamb age and muscle pigment content for 446 lambs from 22 different European production systems, with ages ranging from 1-12 months. Not surprisingly, the age was closely related to weight in that study (r = 0.88) as it would have been in the first experiment of the current work where myoglobin concentrations in all four muscles tested increased with age, particularly between ages of 4 and 8 months (Gardner et al 2007). In contrast, when weight at slaughter was controlled at 32 kg, Ledward and Shorthose (1971) found only a low correlation between muscle myoglobin concentration and age (r = 0.26) for lambs aged from ~100 to 300 days.…”
Section: Meat Tenderness Changes With Agesupporting
confidence: 74%
“…Berge et al (2003) reported a simple correlation of 0.66 between lamb age and muscle pigment content for 446 lambs from 22 different European production systems, with ages ranging from 1-12 months. Not surprisingly, the age was closely related to weight in that study (r = 0.88) as it would have been in the first experiment of the current work where myoglobin concentrations in all four muscles tested increased with age, particularly between ages of 4 and 8 months (Gardner et al 2007). In contrast, when weight at slaughter was controlled at 32 kg, Ledward and Shorthose (1971) found only a low correlation between muscle myoglobin concentration and age (r = 0.26) for lambs aged from ~100 to 300 days.…”
Section: Meat Tenderness Changes With Agesupporting
confidence: 74%
“…This result aligns with work by both Lanari et al (2002) and Yang et al (2002) who found supplemented cattle had a better colour stability than pasture fed animals. Different muscles may vary in initial colour due to differing pigment concentrations (myoglobin), associated with variation in fibre type (Gardner et al, 2007). However in this study, the fibre type of pasture fed lambs is unlikely to have changed significantly compared to other treatments over such a short feeding period.…”
Section: Further Investigation Into Different Aging Periods and Vitammentioning
confidence: 43%
“…concentration from low in the ST, to medium in the LL and high in the SM (Gardner, Hopkins, Greenwood, Cake, Boyce & Pethick, 2007). Muscles can be categorised in to colour stability ranges by considering how quickly that muscle would reach an unacceptable colour for consumers (ratio of 3.5) (Morrissey et al, 2008).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…We present three hypotheses: 1. Muscle pH will have a greater effect on lamb loin lightness than myoglobin and iron concentration or isocitrate dehydrogenase (ICDH) activity, a marker of muscle oxidative capacity (Gardner et al, 2007). 2.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%